Modern Potential of Rural Tourism Development in Kazakhstan - SEKEN, Aday; DUISSEMBAYEV, Azamat; TLEUBAYEVA, Aitolkyn; AKIMOV, Zhaxylyk; KONURBAEVA, Zhadyra; SUIEUBAYEVA, Saltanat (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).03, 2019)
Tourism as an integral part of the life of modern society is a global phenomenon of today. One of the priorities in the field of tourism is rural tourism. In developed countries, this type of tourism has become a highly profitable sector of the tourism industry. According to the WTO, rural tourism is one of the five main strategic directions of tourism development in the world until 2020. The development of rural tourism in many countries is considered to be the key to sustainable development of rural areas.This article discusses the huge potential of rural tourism in Kazakhstan, and each of them is analyzed separately. Thus, the potential of rural tourism is identified and described as agricultural, climatic, organizational and distribution, socio-geographical, cultural and historical, material and technical, institutional and economic (on the part of state and local Executive bodies). In particular, examples from foreign practices are given. Recommendations on the factors hindering the development of rural tourism in Kazakhstan are given.